CHARACTERISTICS OF THE OPTIMIZED MODEL OF MEDICAL CARE FOR THE POPULATION WITH DISEASES OF BLOOD AND BLOOD-FORMING ORGANS AT THE REGIONAL LEVEL - V. V. Horokh (Eastern Ukrainian Medical Journal, 2020)
The article presents an optimized model of medical care for the population with diseases of the blood and blood-forming organs at the regional level in modern conditions of health care reform based on the current legislation of Ukraine on health care reform and scientific literature on the organization of medical care for patients with diseases of the blood and blood-forming organs. The scientific substantiation of the optimized model of hematological medical care at the regional level in the conditions of reforming the health care system of the country was carried out within the existing medical-demographic and socio-economic situation, taking into account the positive changes in the future. The model envisages the structure and organization of medical care for patients at all stages and levels of medical care. The structural basis of the model of providing medical care to patients with diseases of the blood and blood-forming organs is the available resources of the current health care system. Its implementation requires additional financial resources for logistics in accordance with industry standards, which should be provided in the provision of medical care and without the implementation of the proposed model. The model provides a concentration of resources, which determines its economic efficiency. The implementation of the proposed optimized model of medical care for the population with diseases of the blood and blood-forming organs at the regional level will provide the population suffering from these diseases to provide affordable medical care in stages and levels of its provision depending on health status.